Beta2-Adrenergic Receptor Polymorphisms and Haplotypes Associate With Chronic Pain in Sickle Cell Disease - Jhun, Ellie H.; Sadhu, Nilanjana; Hu, Xiaoyu; Yao, Yingwei; He, Ying; Wilkie, Diana J.; Molokie, Robert E.; Wang, Zaijie Jim (Frontiers in Pharmacology, 2019)
Pain in sickle cell disease (SCD) is severe, variable, and inadequately comprehended. The β2-adrenergic receptor (ADRB2) is critical in mediating neurotransmitter response in the sympathetic nervous system. In this association study, we examined 16 single nucleotide polymorphisms (SNPs) covering 5’-UTR and coding regions of ADRB2 for pain variability in SCD. Subjects recorded their non-crisis, baseline pain experience on a computerized tool from which we obtained chronic pain measurement score- composite pain index (CPI). Regression models yielded significant associations between chronic pain and seven SNPs. Nonsynonymous SNP rs1042713 A allele (Arg16) caused a 5.73-fold decrease in CPI (p=0.002). Allele A of rs12654778 and T of rs17778257 reduced CPI by a fold of 4.52 (p=0.019), and 4.39 (p=0.032), respectively. Whereas, in the 5’UTR, allele C of rs1042711, G of rs11168070, C of rs11959427, and C of rs1801704 increased CPI by a fold of 10.86 (p=0.00049), 5.99 (p=0.016), 5.69 (p=0.023), and 5.26 (p=0.031), respectively. Together, these SNPs accounted for 2-15% of CPI variance after adjusting for covariates. Moreover, these SNPs were in high linkage disequilibrium (LD) showing 3 LD blocks in our cohort. A 10-marker haplotype increased CPI by 11.5-fold (p=0.000407). Thus, ADRB2 polymorphisms might contribute to chronic pain severity and heterogeneity in SCD.